Study of the Effect of Bodybuilding and Weightlifting Training On Speed - Altaf Chopadiya; Dr. Vipul Upadhyay (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This research study studied the effect of bodybuilding and weightlifting training on speed. A total of 60 athletes from Ahmedabad district in the age group of 18 to 25 years were selected as subjects in this research study. In this research study, 20 athletes were divided into three groups: 20 athletes in the bodybuilding group, 20 in weightlifting (jerk and snatch) and 20 athletes in the control group. The standard of measurement was speed measurement by running 50 times. To find out the effects on the bodybuilding training group and the weightlifting training group, the Analysis of Covariance test was applied and the differences between the means were tested for significance at the 0.05 level using the Least Significant Difference (Post Hoc) test. The conclusion was as follows. Subjects selected from the twelve (12) week weightlifting and bodybuilding training program showed significant improvement in speed.